2006
DOI: 10.1073/pnas.0503465103
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cardiac L-type Ca 2+ channels to a caveolar macromolecular signaling complex is required for β 2 -adrenergic regulation

Abstract: L-type Ca 2؉ channels play a critical role in regulating Ca 2؉ -dependent signaling in cardiac myocytes, including excitation-contraction coupling; however, the subcellular localization of cardiac L-type Ca 2؉ channels and their regulation are incompletely understood. Caveolae are specialized microdomains of the plasmalemma rich in signaling molecules and supported by the structural protein caveolin-3 in muscle. Here we demonstrate that a subpopulation of L-type Ca 2؉ channels is localized to caveolae in ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
409
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(437 citation statements)
references
References 41 publications
24
409
1
3
Order By: Relevance
“…Previous studies have not only indicated CAV1 to localize with ERα, but also mGluR1a [88]. Similarly, L-type calcium channels cluster in CAV3-generated caveolae [89,90]. As such, we find several individual signaling molecules linked to caveolin proteins to which they were previously ascribed.…”
Section: Caveolin Proteins and Estrogen Receptorssupporting
confidence: 64%
“…Previous studies have not only indicated CAV1 to localize with ERα, but also mGluR1a [88]. Similarly, L-type calcium channels cluster in CAV3-generated caveolae [89,90]. As such, we find several individual signaling molecules linked to caveolin proteins to which they were previously ascribed.…”
Section: Caveolin Proteins and Estrogen Receptorssupporting
confidence: 64%
“…In this context, the overexpression of Myoscape resulted in enhanced global calcium transients with higher calcium amplitudes and LTCC currents. These results were additive to the effects of isoproterenol, implying that Myoscape acts independently of the adrenergic control of LTCC activity via PKA-dependent phosphorylation91326. Conversely, Myoscape ablation reduced LTCC currents irrespective of beta-adrenergic costimulation, which is associated with reduced global calcium transients and impaired contractile performance of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 88%
“…Exogenous NO (i.e., NO donors) and nonspecific NOS inhibitors have also been shown to regulate ␤-AR-stimulated I Ca (33,48), and it was hypothesized that this effect was via NOS3. Within cardiac myocytes, NOS3 is localized with the L-type Ca 2ϩ channel and the ␤ 2 -AR receptor to the caveolae (3,17). However, studies investigating ␤-ARstimulated I Ca in NOS3 Ϫ/Ϫ myocytes observed no difference compared with WT myocytes (21, 46).…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 98%
“…Exogenous NO (i.e., NO donors) has also been found to decrease ␤-AR-stimulated I Ca (48). NOS3 is localized to the caveolae, along with the L-type Ca 2ϩ channel and the ␤ 2 -AR receptor (3,17). In addition, a study showed that myocytes from female mouse hearts have smaller ␤-AR -induced I Ca and a higher association between NOS3 and caveolin-3 compared with myocytes from male mouse hearts (43).…”
mentioning
confidence: 99%